A description of the nymph of Anacroneuria ofaye Froehlich (Plecoptera: Perlidae) and a apparatus for rearing Neotropical stonefly species - Novaes, Marcos Carneiro; Da Conceição Bispo, Pitágoras; Higuti, Janet (Zootaxa, 2012)
The Neotropical genus Anacroneuria (Perlidae) is represented by more than 300 species. Among the Brazilian Anacroneuria, only the nymphs of two species have been described. In this paper, we described the nymph of A. ofaye Froehlich and an apparatus for rearing this genus. This is the first record of A. ofaye from Paraná State, Brazil.